2011
DOI: 10.1016/j.sjbs.2010.12.001
|View full text |Cite
|
Sign up to set email alerts
|

Determination of heavy metals in the fruit of date palm growing at different locations of Riyadh

Abstract: Exposure of heavy metals to human beings has risen dramatically in the last 50 years. In today's urban and industrial society, there is no escaping from exposure to toxic chemicals and heavy metals. Humans are more likely to be exposed to heavy metal contamination from the dust that adheres to edible plants than from bioaccumulation. This is because it is very difficult to wash off all the dust particles from the plant material before ingesting them. The objectives of this experiment were to determine the conc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
35
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(37 citation statements)
references
References 17 publications
2
35
0
Order By: Relevance
“…However, in several previous studies, higher levels of lead were found in fruit and fruity vegetable samples produced or sold in Saudi markets (Aldjain et al 2010;Ali & Al-Qahtani 2012;KAIRCS 2004;Mohamed et al 2003).…”
Section: Leadmentioning
confidence: 85%
“…However, in several previous studies, higher levels of lead were found in fruit and fruity vegetable samples produced or sold in Saudi markets (Aldjain et al 2010;Ali & Al-Qahtani 2012;KAIRCS 2004;Mohamed et al 2003).…”
Section: Leadmentioning
confidence: 85%
“…Aldjain et al [21] determined the concentration of lead (Pb) and cadmium (Cd) in washing residues and in the tissues of fruits of date palm growing in 14 sites of Riyadh. They stated that humans are likely to be exposed to heavy metal contamination from the dust that adheres to edible plants than from bioaccumulation.…”
Section: Mineral Compositionmentioning
confidence: 99%
“…A very important step is the washing of samples after collection. The use of tap water (Al Hooti et al 1997) or double-distilled water (Sulieman et al 2012;Aldjain et al 2011;Taha and Ghtani 2015) instead of deionized water results in a relatively high level of the blank sample, which may make it impossible to detect trace elements. The drying stage is also very important.…”
Section: Elemental Composition and Antioxidant Properties Of Dates' Pmentioning
confidence: 99%
“…Consumption of 100 g of dates provides 15% of the daily demand for selenium, copper, potassium and magnesium (Al-Showiman 1998). Many researchers focused in their experiments on determining the elemental composition of dates from various regions: Spain (Abdrabo et al 2015), Oman (Al Farsi and Lee 2008), Saudi Arabia (Aldjain et al 2011;Assirey 2015;Hamad et al 2015;Mohamed 2000), Sudan (Mohamed et al 2014;Sulieman et al 2012). The scientists focused on determination elements that are essential for human organism as well as toxic.…”
Section: Introductionmentioning
confidence: 99%